Comparison of SENSIMED Triggerfish® (TF) 24-Hour Monitoring in Open-Angle Glaucoma Patients Before and After Trabeculectomy - Anna Beck; Michael Uhrig; Alexander Schuster; Christina A. Korb; Norbert Pfeiffer; Katrin Lorenz (2025)
Background/Objectives: In glaucoma patients, the fluctuation in intraocular pressure during the day seems to have an influence on the progression of the disease. The contact lens sensor (CLS) Triggerfish® from the company SENSIMED records ocular dimensional changes for 24 h. The aim was to determine the amplitude of the measurements with a contact lens sensor before and after trabeculectomy (TE) in glaucoma patients. Methods: Twelve patients with glaucoma were included in this prospective, single-arm, single-center, interventional study. All patients received a CLS measurement for 24 h 8 ± 2 days before and 12 weeks (±1 week) after surgery. The raw data of the measurements were modeled using a double-harmonic cosine function. Fluctuation in the raw CLS data, amplitude, and the MESOR (midline estimating statistic of rhythm, rhythm-adjusted mean) of the modeled data were investigated. The safety and feasibility of the CLS measurements were evaluated. Results: Nine patients underwent the complete 24-h wearing period before and after surgery. Whereas the MESOR changed significantly before and after surgery (p = 0.04), the amplitude of the modeled data did not change significantly and the daytime fluctuation and circadian rhythm also did not vary significantly. The CLS could be safely removed from all study eyes after surgery. Conclusions: The non-significant change in amplitude suggests that diurnal fluctuations persist after TE. This contrasts with reports in the literature that show that TE reduces diurnal fluctuations. It can be assumed that the significant reduction in the MESOR represents the reduction in the average intraocular pressure over 24 h. The CLS can be used safely three months after TE.